2007
DOI: 10.1086/521086
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Levels and Body Composition of Mice Selectively Bred for High Voluntary Locomotor Activity

Abstract: Selective breeding produced four replicate lines of high-runner (HR) mice that run on wheels for approximately 2.7 times more revolutions per day than four unselected control lines. Previous studies found that HR mice of both sexes have lower body fat (isotope dilution at 15 wk of age) and that males (females not studied) have smaller retroperitoneal fat pads (17 wk). HR mice also exhibit elevated plasma corticosterone and insulin-stimulated glucose uptake by some hindlimb muscles but apparently do not differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 79 publications
2
40
1
Order By: Relevance
“…24h) can be quantified as total revolutions, the amount of time activity and/or the average intensity of activity (e.g. Girard et al, 2007;Dlugosz et al, 2009;Gomes et al, 2009;Rezende et al, 2009). With video analysis, details of individual running bouts and the degree of intermittent locomotion can be quantified ) (see also Waters et al, 2008).…”
Section: Defining Voluntary Exercise and Spamentioning
confidence: 99%
See 2 more Smart Citations
“…24h) can be quantified as total revolutions, the amount of time activity and/or the average intensity of activity (e.g. Girard et al, 2007;Dlugosz et al, 2009;Gomes et al, 2009;Rezende et al, 2009). With video analysis, details of individual running bouts and the degree of intermittent locomotion can be quantified ) (see also Waters et al, 2008).…”
Section: Defining Voluntary Exercise and Spamentioning
confidence: 99%
“…Another factor adding complexity is that genotype-environment interactions are likely to be common (see also Dishman, 2008). For example, the relationships between physical activity, energy intake and body composition can differ dramatically between the sexes, among individual humans and among strains of mice, and the effects of exercise training are also known to vary among individual humans in relation to genotype Melzer et al, 2005;Girard et al, 2007;Vaanholt et al, 2008;Nehrenberg et al, 2009a;Jung and Luthin, 2010;Jung et al, 2010;Meek et al, 2010;Timmons et al, 2010). As noted in the previous section, wheel access usually, but not always, reduces body fat in rodents, especially in males.…”
Section: Energy Intake Physical Activity and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mice selectively bred for increased wheel-running activity are leaner than control line animals and have relatively low circulating leptin levels but high adiponectin levels. [16][17][18] Even without the presence of a running wheel, these genetically selected animals display increased locomotor activity, 19 and therefore may represent a relevant model for the study of increased spontaneous activity in the development of HFD-induced obesity and metabolic derangements. Recently, we observed that males from this breeding line have higher plasma adiponectin levels in the adult and aged state when they were eating a regular highcarbohydrate diet (HCD) and this difference was found in animals with or without access to running wheels.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent work in human 'ultra-endurance' athletes (Pearson, 2006) suggests that neurobiological attributes make a greater contribution to maximum performance ability than has previously been acknowledged (Kayser, 2003;Baden et al, 2005;Noakes, 2007;Rose and Parfitt, 2007;Noakes, 2008). In our laboratory, selection for high voluntary wheel running in outbred laboratory house mice has been ongoing for more than 60 generations, and has resulted in numerous physiological (Girard et al, 2007;Malisch et al, 2008;Gomes et al, 2009;Meek et al, 2009), behavioral (Rhodes et al, 2001Rhodes and Garland, 2003; Belke and Garland, 2007;Meek et al, 2010), and neurobiological (Rhodes et al, 2003a;Rhodes et al, 2003b) changes in four replicate high-runner (HR) lines of mice as compared with four non-selected control (C) lines. Moreover, a recent comparative study demonstrated a positive correlation between brain size and an index of exercise capacity, maximal oxygen consumption (Raichlen and Gordon, 2011), one of the traits that has increased in the HR lines (Rezende et al, 2006b;Kolb et al, 2010).…”
mentioning
confidence: 98%